Sertoli cell tumor in a cryptorchid dog - Kisani, Aboh Iku; Wachida, Ndumari; Apaa, Ternenge Thaddaeus; Ahur, Victor Masekaven; Grema, Barka Allabeh; Tughgba, Terzungwe; Adamu, Simon Shaibu; Rabo, Jude Sammani (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This case report describes the surgical management of a clinical case of sertoli cell tumor in a Lhasa Apso breed of dog Materials and methods: A 4-year old sexually intact Lhasa apso was presented with complaints of alopecia, shivering, reduced appeteite and swelling of the inguinal region. The dog was subjected to thorough physical, Hematological, Histopathological and Radiographic evaluations. Results: The vital parameters were within normal values. Hematological analysis revealed anemia and thrombocytopenia as the common findings. Abdominal radiography showed a soft tissue mass in the inguinal region. Histopathology revealed testicular hypoplasia with poorly developed seminiferous tubule with no discernible lumen or spermatozoa and several proliferating sertoli cells on the lining of the basement membrane of the seminiferous tubules which is diagnostic of sertoli cell tumor. Decision to surgically excise the tumor was arrived at. The anesthetic protocol involved premedication with atropine sulphate dosed at 0.04 mg/kg bwt and xylazine dosed at 2 mg/kg bwt intramuscularly (IM). Anesthesia was induced and maintained with propofol dosed at 6 mg/kg bwt intravenously (IV). The tumor mass was surgically excised. Broad spectrum antibiotics (penstrep) and analgesic (pentazocine) were administered for 5 days IM. Conclusion: The condition of the dog improved remarkably and it was discharged on postoperative day 10. http://doi.org/10.5455/javar.2017.d237